The effects of antioxidants on knee osteoarthritis: A systematic review and meta-analysis - Nejadhosseinian, Mohammad; Djalalinia, Shirin; Haerian, Hoda; Alikhani, Majid; Mansour, Asieh; Mousavian, Amir-Hossein; Mardani-Fard, Heydar Ali; Kasaeian, Amir; Faezi, Seyedeh Tahereh (Frontiers in Nutrition, 2022)
Objective: Knee osteoarthritis (OA) is one of the increasing health problems with considerable burden. With recent investigations on probable effectiveness of antioxidants in knee OA symptoms remission, a systematic review and meta-analysis was required to confirm this hypothesis. Design: Literature search was performed through the most comprehensive related data base of PubMed, International Scientific Indexing, and Scopus, without restriction for language and time. The strategy for searches was developed based on the roots of “osteoarthritis” and “antioxidants” without any limitation for time or language at 17 July 2021. As the primary outcomes, pain evaluated based on all indicators for evaluating pain (e.g., Western Ontario and McMaster Osteoarthritis Index (WOMAC) pain scores, the visual analogue scale (VAS), and the numerical rating scale (NRS)). The symptoms, functions of knee OA and quality of life (QOL), were also considered as secondary outcomes, each of which was measured and reported by the corresponding instruments in the studies. Aimed to measuring changes in pain, symptoms and functions of participants, we included randomized controlled trials, with a placebo control or any other medical therapeutic interventions. Publication bias was assessed using the Begg’s funnel plot and Egger’s regression test which was deemed statistically significant at 0.1 and the results were checked by the Trim-and-Fill test. Results: From primary 7,698 searched papers, after refinement processes, data were extracted from 31 documents. Using the visual analogue scales (VAS) as reliable psychometric measuring instruments, present investigation revealed a significant difference in the characteristics of disease-related symptom of patients with KOA have been reached after antioxidant therapy (SMD: 0.467, 95%CI: 0.303 - 0.632), P<0.0001). Results reported by Western Ontario and McMaster Universities Arthritis Index (WOMAC); did not confirm any significant difference in the combined score, difficulty score, pain score and stiffness score. Conclusion: As the first comprehensive systematic review of association between antioxidant supplementation on KOA; antioxidants can decrease the disease-related symptoms of patients with knee OA. Results could be useful for health policy decisions and future similar studies. Systematic review registration: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022351060, Identifier: CRD42022351060